Efek Senyawa Immunomodulator dari Rumput Laut pada Hewan : Literature Review - Alinda Syifa Fumizuki (Jurnal Ilmu Kesehatan dan Gizi, 2025)
The immune system plays a role in protecting the body from foreign antigens that invade. Research on the immune system continues to evolve, especially during the Covid-19 pandemic. Various studies have been conducted on substances and compounds with bioactivity as immunomodulators, which aim to enhance immune responses. One potential source of immunomodulator compounds is seaweed. This study aims to determine the effects of various types of seaweed on enhancing animal immune responses. The study was conducted using a literature review method of previous primary studies. Articles were searched using online databases PubMed and ScienceDirect. Seven articles were used in this study. The three groups of seaweed—red, brown, and green seaweed—demonstrated effects in enhancing immune responses in animals, as seen from the increased levels of IgA, IgG, and IgM, as well as Th1 expression. However, there are no recommendations for the optimal dose of seaweed to enhance immune responses.